Sodium ion battery with low CB value
By using a layered transition metal oxide positive electrode material and a carbon material negative electrode material with a clad layer in sodium ion batteries, combining ether electrolyte and specific electrolyte components, the problems of energy density and cycling performance of low CB value batteries are solved. The uniformity of sodium deposition and the high energy density and stability of the battery are achieved.
Patent Information
- Application Number
- CN202411341960.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-25
- Publication Date
- 2025-01-10
AI Technical Summary
Existing low CB value sodium ion batteries are difficult to meet the requirements of high energy density and good cycling performance at the same time.
The layered transition metal oxide with a cladding layer on the surface is used as the positive electrode material, the carbon material is used as the negative electrode material, and an ether electrolyte is used to control the CB value in the range of 0.1-0.5, and the ID/IG of the negative electrode material is 0.3-0.9. The electrolyte contains NaPF6, NaBF4 and oxalate. The puncture resistance of the separator exceeds 500 gf to improve the uniformity of sodium deposition and the cycle stability of the battery.
The energy density and cycle stability of sodium ion batteries at lower CB values are improved, ensuring uniformity of sodium deposition, reducing side reactions, and extending battery life.
Smart Images

Figure BDA0005059956510000101
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of sodium ion batteries, and in particular to a sodium ion battery with a low CB value. Background Art
[0002] Compared with lithium-ion batteries, sodium-ion batteries have certain cost advantages, but their energy density is relatively low, so the watt-hour cost has not decreased. In order to further reduce the watt-hour cost, the energy density of the battery needs to be increased. The common method to increase capacity density is to use high-capacity positive and negative electrode materials, but the development cycle of high-capacity materials is long and the cost is relatively high, so the effect on reducing the watt-hour cost is relatively small. Using no negative electrode or reducing the battery CP value is a relatively radical improvement method, which has obvious effects but poor cycle performance. Summary of the invention
[0003] In view of the above analysis, the present invention aims to provide a sodium ion battery with a low CB value, so as to solve the problem that the sodium ion battery with a low CB value in the prior art cannot meet both high energy density and good cycle performance.
[0004] In order to achieve the above object, the present invention adopts the following technical solution:
[0005] A low CB value sodium ion battery comprises a positive electrode sheet, a negative electrode sheet, an electrolyte and a separator, wherein the CB value of the sodium ion battery is 0.1-0.5, the positive electrode material of the positive electrode sheet is a layered transition metal oxide with a coating layer on the surface, the negative electrode material of the negative electrode sheet is a carbon material, the ID / IG of the carbon material is 0.3-0.9, and the electrolyte is an ether electrolyte.
[0006] Furthermore, the moisture content of the positive electrode sheet is less than 150 ppm, the moisture content of the negative electrode sheet is less than 150 ppm, and the porosity of the negative electrode sheet is greater than 40%.
[0007] Furthermore, the coating layer includes C, Al 2 O 3 , phosphate or sulfate.
[0008] Furthermore, the ether is diethylene glycol dimethyl ether or DME.
[0009] Furthermore, the electrolyte also includes NaPF 6 and NaBF 4 .
[0010] Furthermore, the electrolyte also includes oxalate.
[0011] Furthermore, NaPF 6 , NaBF4 The molar concentration ratio of oxalate is 0.85-0.9:0.05-0.1:0.05-0.1.
[0012] Furthermore, the oxalate is one or more of sodium dioxalyl difluorophosphate, LiBODFP, sodium bis(oxalate)borate, and sodium tri(oxalate)phosphate.
[0013] Furthermore, the electrolyte injection coefficient of 2g / Ah<3.8g / Ah.
[0014] Furthermore, the puncture resistance of the diaphragm is greater than 500 gf.
[0015] Compared with the prior art, the present invention can achieve at least one of the following beneficial effects:
[0016] (1) In the present invention, by selecting specific positive electrode materials, negative electrode materials and electrolytes, the prepared battery is conducive to the uniformity of sodium deposition at a lower CB value, thereby forming a sodium ion battery with higher energy density and better cycle stability. Since the CB in the present invention is a low-level value of 0.1-0.4, there are higher requirements for the uniformity of reaction activity at this time, so it is necessary to provide reaction sites with uniform electrochemical reaction as much as possible. The negative electrode material ID / IG of the present invention is 0.3-0.9. At this time, the negative electrode material has a high degree of crystallinity and very few defects, and the deposition of sodium is relatively uniform. At the same time, the carbon layer spacing is small, and the capacity of the negative electrode material is low or very low. Therefore, sodium is basically deposited on the surface of the material. Fewer defects and better electronic conductivity make the material conducive to the uniformity of sodium deposition;
[0017] (2) The positive electrode material in the present invention mainly contains oxides of transition metal elements. During the cycle process, the transition metal elements are easily partially dissolved as the positive electrode structure changes. The dissolved metal elements will damage the SEI of the negative electrode material, thereby aggravating the side reactions of the negative electrode. Therefore, it is necessary to appropriately coat the positive electrode material to reduce the dissolution of the transition metal elements, among which C, Al 2 O 3 As well as phosphates and sulfates, since they can increase the electronic conductivity or ionic conductivity of the positive electrode material, which is beneficial to the battery cycle, the above materials are selected to coat the positive electrode.
[0018] In the present invention, the above-mentioned technical solutions can also be combined with each other to achieve more preferred combination solutions. Other features and advantages of the present invention will be described in the subsequent description, and some advantages can become obvious from the description, or can be understood by practicing the present invention. The purpose and other advantages of the present invention can be achieved and obtained through the contents particularly pointed out in the description. DETAILED DESCRIPTION
[0019] A specific embodiment of the present invention discloses a low CB value sodium ion battery, comprising a positive electrode sheet, a negative electrode sheet, an electrolyte and a separator, wherein the CB value of the sodium ion battery is 0.1-0.5 (for example, 0.1, 0.2, 0.3, 0.4, 0.5), the positive electrode material of the positive electrode sheet is a layered transition metal oxide having a coating layer on the surface, the negative electrode material of the negative electrode sheet is a carbon material, and the ID / IG of the carbon material is 0.3-0.9 (for example, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9), and the electrolyte is an ether electrolyte.
[0020] The CB value used in the prior art battery design is generally between 1.0-1.2, that is, the ratio of the negative electrode capacity to the positive electrode capacity per unit area is between 1.0-1.2, and the negative electrode capacity is higher than the positive electrode capacity to prevent sodium precipitation. Since the capacity of the battery is determined by the amount of the positive electrode, the present invention makes the negative electrode capacity per unit area of the battery much lower than the positive electrode capacity, thereby reducing the proportion of the negative electrode in the battery and greatly increasing the proportion of the positive electrode, so that the capacity of the battery can be increased, and the energy density of the battery can be indirectly increased. Since the negative electrode capacity in the present invention is relatively low and the sodium storage capacity is low, it only serves as a substrate for depositing sodium metal, so the CB value is low.
[0021] In the present invention, by selecting specific positive electrode materials, negative electrode materials and electrolytes, the prepared battery is conducive to the uniformity of sodium deposition at a lower CB value, thereby forming a sodium ion battery with higher energy density and better cycle stability. This is because the uneven sodium deposition layer will form dendrites, which will penetrate the diaphragm and cause the battery to short-circuit directly, and will also increase the side reaction between the sodium deposition layer and the electrolyte, and basically have no circulation capacity. Since CB in the present invention is a low-level value of 0.1-0.4, there are higher requirements for the uniformity of reaction activity at this time, so it is necessary to provide reaction sites with uniform electrochemical reaction as much as possible. The negative electrode material ID / IG of the present invention is 0.3-0.9. At this time, the negative electrode material has a high crystallinity and few defects, and the deposition of sodium is relatively uniform. At the same time, the carbon layer spacing is small, and the capacity of the negative electrode material is low or very low. Therefore, sodium is basically deposited on the surface of the material, and fewer defects have better electronic conductivity at the same time, so that the material contributes to the uniformity of sodium deposition.
[0022] In a specific embodiment, the moisture content of the positive electrode sheet is less than 150 ppm, the moisture content of the negative electrode sheet is less than 150 ppm, and the porosity of the negative electrode sheet is greater than 40%.
[0023] It should be noted that relatively large porosity can reduce the obstruction to the electrolyte and sodium deposition, so that the sites of sodium ions can be evenly distributed on the surface and inside the coating, which is also conducive to the uniformity of sodium deposition. The presence of water will strengthen the side reaction between the sodium deposition layer and the electrolyte, which needs to be avoided as much as possible; therefore, an oil system is used to reduce the contact between the negative electrode material and water, so that the moisture content of the electrode is controlled at a lower level, and the moisture content of the positive electrode should also be controlled at a lower level.
[0024] In a specific embodiment, the coating layer includes C, Al 2 O 3 , phosphate or sulfate.
[0025] Specifically, the phosphate is one or more of sodium iron phosphate, sodium vanadium phosphate, sodium iron pyrophosphate or sodium titanium phosphate, the sulfate is sodium iron sulfate, and the layered transition metal oxides with coating layers described in the present invention are all prepared by existing methods or commercially available raw materials, for example, the layered transition metal oxides are coated with the method of patent CN117936748A. C, Al 2 O 3 , phosphates or sulfates can increase the electronic conductivity or ionic conductivity of the positive electrode material, which is beneficial to the battery cycle.
[0026] The positive electrode material in the present invention mainly contains oxides of transition metal elements. During the cycle process, the transition metal elements are easily partially dissolved as the positive electrode structure changes. The dissolved metal elements will damage the SEI of the negative electrode material, thereby aggravating the side reactions of the negative electrode. Therefore, it is necessary to properly coat the positive electrode material to reduce the dissolution of the transition metal elements. 2 O 3 As well as phosphates and sulfates, since they can increase the electronic conductivity or ionic conductivity of the positive electrode material, which is beneficial to the battery cycle, the above materials are selected to coat the positive electrode.
[0027] In a specific embodiment, the ether is diethylene glycol dimethyl ether or DME.
[0028] In a specific embodiment, the electrolyte further comprises NaPF 6 and NaBF 4 .NaPF 6 and NaBF 4 It can help form a relatively stable surface SEI protective film and also reduce the occurrence of side reactions.
[0029] In a specific embodiment, the electrolyte further includes oxalate, and the oxalate is one or more of sodium dioxalate difluorophosphate, LiBODFP, sodium bis(oxalate)borate, and sodium tri(oxalate)phosphate. This is because the above substances can cooperate with the metal elements dissolved from the positive electrode to prevent the transition metal elements from diffusing to the negative electrode to destroy the negative electrode SEI film.
[0030] It should be noted that the ether electrolyte is conducive to forming a uniform and smooth sodium deposition layer and is not easy to have side reactions with the sodium deposition layer, which is beneficial to the stability of the entire system, while NaBF 4 It can help form a relatively stable surface SEI protective film and also reduce the occurrence of side reactions.
[0031] In a specific embodiment, NaPF 6 , NaBF 4 The molar concentration ratio (mol / L) of oxalate is 0.85-0.9:0.05-0.1:0.05-0.1, for example, 0.85:0.1:0.05, 0.86:0.8:0.06, 0.87:0.07:0.07, 0.9:0.05:0.1.
[0032] In a specific embodiment, the injection coefficient of the electrolyte is 2g / Ah<3.8g / Ah, for example, 2.1g / Ah, 2.3g / Ah, 2.5g / Ah, 2.7g / Ah, 2.9g / Ah, 3.1g / Ah, 3.3g / Ah, 3.4g / Ah, 3.5g / Ah, 3.6g / Ah, 3.7g / Ah, and 3.8g / Ah.
[0033] The filling coefficient is set mainly because during the circulation process, a small number of side reactions still occur between the sodium metal precipitated in the later stage and the electrolyte. Therefore, the amount of electrolyte injection cannot be too small. If it is too little, the amount of electrolyte will be insufficient in the later stage of the cycle. However, it cannot be too much either, because the side reactions will produce gas. If there is too much electrolyte, there will be less space for gas in the cylindrical shell, and the cylinder is easy to flip over.
[0034] In a specific embodiment, the puncture resistance of the diaphragm is greater than 500 gf.
[0035] Specifically, higher puncture resistance can prevent the presence of slightly uneven deposition in some areas, thereby preventing sodium metal from puncturing the diaphragm and preventing short circuits from causing battery failure.
[0036] The low CB value sodium ion battery of the present invention has a battery capacity of 3950-5952 mAh / g, a battery energy density of 151.1-222.3 Wh / kg, and a capacity retention rate of 82.7-91.7% after 100 cls of cycling at room temperature and 0.5C.
[0037] Another specific embodiment of the present invention discloses a method for preparing a low CB value sodium ion battery, comprising the following steps:
[0038] (a) Preparation of positive electrode sheet: positive electrode material, binder, conductive agent and solvent are mixed, coated on aluminum foil, compacted and cut to obtain positive electrode sheet;
[0039] (b) Preparation of negative electrode sheet: negative electrode material, binder, conductive agent and solvent are mixed, coated on aluminum foil, compacted and cut to obtain negative electrode sheet;
[0040] (c) Preparation of battery: The positive electrode sheet, negative electrode sheet and separator are placed in a shell, and an electrolyte is added, the shell is sealed and activated to obtain the sodium ion battery.
[0041] The technical scheme of the present invention is further explained in conjunction with specific embodiments. The raw materials in the following embodiments are all commercially available raw materials. Among them, the carbon material manufacturer is Hunan Naco New Materials Co., Ltd., Al 2 O 3 The preparation method of the coated NFM424 layered oxide positive electrode material is prepared according to patent CN117936748A. The manufacturer of the 12+2+2 separator is the SW16 series of Shenzhen Xingyuan Material Technology Co., Ltd., and the manufacturer of the 12μm base film is the E10 series of Shenzhen Xuran Electronics Co., Ltd. The above models are used as examples for explanation in the present invention, and the protection scope of the present invention is not limited to this.
[0042] Example 1
[0043] A low CB value sodium ion battery of this embodiment, the specific preparation method is as follows:
[0044] Preparation of positive electrode: Al 2 O 3 The coated NFM424 layered oxide positive electrode material was mixed with the binder PVDF, the conductive agent SP, the CNT, and the oxalic acid in the mass percentage of 95.5%:1.7%:2.0%:0.5%:0.3% with NMP as the solvent. After being mixed evenly, the single-sided surface density was 16.5 mg / cm 2 The positive electrode sheet is formed by coating on aluminum foil, and the positive electrode sheet is rolled to a compaction density of 3.25 g / cc. The rolled positive electrode sheet is cut into strips to obtain the required positive electrode sheet.
[0045] Preparation of negative electrode: Ordered carbon material (ID / IG = 0.35) was mixed with adhesive PVDF, conductive agent SP and CNT in a mass percentage of 94.5%: 3%: 2%: 0.5% using NMP as solvent. After mixing evenly, the mixture was plated with a single surface density of 6.5 mg / cm 2 The negative electrode sheet is formed by coating on aluminum foil, and the negative electrode sheet is rolled to have a compaction density of 1.3 g / cc. The rolled negative electrode sheet is cut into strips to obtain the required negative electrode sheet, and the porosity of the negative electrode sheet is 41%.
[0046] Preparation of the battery: The positive and negative electrodes and the 12+2+2 separator (with a puncture resistance of 600gf) are welded to the ears and wound into the shell. The opened battery cells are baked to meet the conditions of moisture content of the positive electrode <150ppm and moisture content of the negative electrode <150ppm. The battery cells are injected with liquid (injection coefficient is 3Ah / g). The electrolyte uses diethylene glycol dimethyl ether as the solvent and NaPF 6 , NaBF 4 , LiBODFP are mixed in a molar concentration ratio of 0.85:0.1:0.05, and then a sealing process is performed, and the battery after injection is activated to obtain the required battery, and the CB value of the battery is 0.29.
[0047] Example 2
[0048] The preparation method of the sodium ion battery of this embodiment is the same as that of embodiment 1, except that the positive electrode material is a NFM424 layered oxide positive electrode material coated with sodium titanium phosphate;
[0049] The sodium titanium phosphate coated NFM424 layered oxide positive electrode material is prepared by the following method: 16 H 36 O 4 Ti、Na 2 CO 3 NH 4 H 2 PO 4 The mixture was dispersed in 30 mL of deionized water at a molar concentration ratio of 2:1:2, and 25 wt% of citric acid was added in small amounts and multiple times at 80°C to obtain a mixed solution; the NFM424 precursor was sintered at 500°C for 12 hours, and the mixture was added to the mixed solution, stirred evenly and dried, and sintered in a dry air atmosphere at 900°C to obtain a sodium titanium phosphate-coated NFM424 layered oxide positive electrode material.
[0050] Example 3
[0051] The preparation method of the sodium ion battery of this embodiment is the same as that of embodiment 1, except that the single-surface density is 19.5 mg / cm 2 Coated on aluminum foil to form the positive electrode sheet, the carbon material ID / IG on the negative electrode sheet is 0.8, with a single-sided surface density of 4.8 mg / cm 2 The negative electrode sheet is formed by coating on aluminum foil, and the negative electrode sheet is roll-pressed, with a compaction density of 0.92 g / cc, a porosity of 43%, and a CB value of 0.3.
[0052] Example 4
[0053] The preparation method of the sodium ion battery of this embodiment is the same as that of embodiment 1, except that the single surface density is 19 mg / cm 2 Coated on aluminum foil to form the positive electrode sheet, the carbon material ID / IG on the negative electrode sheet is 0.35, with a single-sided surface density of 5 mg / cm 2 The negative electrode sheet is coated on aluminum foil and rolled, with a compaction density of 1.3 g / cc, a porosity of 42%, and a CB value of 0.19.
[0054] Example 5
[0055] The preparation method of the sodium ion battery of this embodiment is the same as that of embodiment 1, except that the single surface density is 12 mg / cm 2 Coated on aluminum foil to form a positive electrode sheet with a single-sided surface density of 8 mg / cm 2 Coated on aluminum foil to form a negative electrode plate, the CB value of the battery is 0.5.
[0056] Comparative Example 1
[0057] The preparation method of the sodium ion battery of this embodiment is the same as that of Embodiment 1, except that the compaction density of the negative electrode plate is 1.6 g / cc, and the porosity of the plate is 26%.
[0058] Comparative Example 2
[0059] The preparation method of the sodium ion battery in this embodiment is the same as that in embodiment 1, except that the single-surface density is 20 mg / cm 2 Coated on aluminum foil to form a positive electrode sheet with a single-sided surface density of 5 mg / cm 2 A negative electrode sheet is formed by coating on aluminum foil, in which the carbon material ID / IG is 1.03, the compaction density of the negative electrode sheet is 0.92 g / cc, the porosity of the negative electrode sheet is 45%, and the CB value of the battery is 0.44.
[0060] Comparative Example 3
[0061] The preparation method of the sodium ion battery in this embodiment is the same as that in embodiment 1, except that the single-surface density is 12 mg / cm 2 Coated on aluminum foil to form a positive electrode sheet with a single-sided surface density of 10.5 mg / cm 2 A negative electrode sheet is formed by coating on aluminum foil, in which the carbon material ID / IG is 0.8, the compaction density of the negative electrode sheet is 0.92 g / cc, the porosity of the negative electrode sheet is 43%, and the CB value of the battery is 1.07.
[0062] Comparative Example 4
[0063] The preparation method of the sodium ion battery of this embodiment is the same as that of Embodiment 1, except that the injection coefficient is 4 Ah / g.
[0064] Comparative Example 5
[0065] The preparation method of the sodium ion battery of this embodiment is the same as that of embodiment 1, except that, in the preparation of the negative electrode sheet, the ordered carbon material (ID / IG=0.35) is mixed with the dispersant CMC, the binder SBR, and the conductive agent SP in a ratio of 94.7%:2%:2.8%:0.5% with water as the solvent, and after being mixed evenly, the mixture is heated to a temperature of 600 °C with a single surface density of 6.5 mg / cm 2 Coating on aluminum foil to form a negative electrode sheet, and rolling the negative electrode sheet to a compaction density of 1.3 g / cc, and cutting the rolled negative electrode sheet into strips to obtain the required negative electrode sheet;
[0066] During battery manufacturing, the moisture content of the negative electrode is 264ppm.
[0067] Comparative Example 6
[0068] The preparation method of the sodium ion battery of this embodiment is the same as that of Embodiment 1, except that the positive electrode material is NFM424 layered oxide positive electrode material.
[0069] Comparative Example 7
[0070] The preparation method of the sodium ion battery in this embodiment is the same as that in embodiment 1, except that the NaPF 6 , NaBF 4 , LiBODFP molar concentration ratio is 0.6:0.2:0.2.
[0071] Comparative Example 8
[0072] The preparation method of the sodium ion battery of this embodiment is the same as that of Embodiment 1, except that the 12+2+2 separator is replaced by a 12 μm base film, and the puncture resistance strength of the base film is 300 gf.
[0073] Test Example 1
[0074] The electrical properties of the sodium ion batteries prepared in Examples 1-5 and Comparative Examples 1-8 were tested respectively, and the results are shown in Table 1. Among them, the test method for the retention rate of 100 cls cycle at room temperature and 0.5C is as follows:
[0075] 1. The battery is discharged at 0.5C constant current to 2V Rest for 10min;
[0076] 2. 0.5C constant current and constant voltage charge to 4.25V Rest 10min;
[0077] 3. 0.5C constant current discharge to 2V Rest 10min;
[0078] 4. Cycle steps 2-3 for 100 cls, record the discharge capacity of the 3rd cycle as C3, and record the discharge capacity of the 100th cycle as C100 (retention rate of 100 cls cycle at room temperature 0.5C = C100 / C3).
[0079] Table 1
[0080]
[0081] Comparative Example 1 Compared with Example 1, the cycle performance of the battery prepared by the porosity of the negative electrode sheet is not within the scope of the present invention, which is significantly reduced. Comparative Example 2 Compared with Example 1, the cycle performance of the battery prepared by the carbon material ID / IG in the negative electrode sheet is not within the scope of the present invention, which is significantly reduced. Comparative Example 3 Compared with Example 1, the battery energy density of the battery prepared by the CB value of the battery not within the specified range of the present invention is reduced. Comparative Example 4 Compared with Example 1, the activation flip of the battery prepared by the injection coefficient not within the scope of the present invention fails. Comparative Example 5 Compared with Example 1, when the moisture content of the negative electrode sheet is high, the cycle performance of the prepared battery is reduced. Comparative Example 6 Compared with Example 1, when the surface of the positive electrode material is not coated with a coating layer, the energy density is slightly higher, but the cycle performance of the battery is reduced. Comparative Example 7 Compared with Example 1, the cycle performance of the battery prepared by the components in the electrolyte not within the scope of the present invention is reduced. Comparative Example 8 Compared with the examples, the battery prepared by using a base film with low puncture resistance fails in a short circuit.
[0082] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily conceived by any technician familiar with the technical field within the technical scope disclosed by the present invention should be covered within the protection scope of the present invention.
Claims
1. A low CB value sodium ion battery, characterized in that: The invention comprises a positive electrode sheet, a negative electrode sheet, an electrolyte and a separator. The CB value of the sodium ion battery is 0.1-0.
5. The positive electrode material of the positive electrode sheet is a layered transition metal oxide with a coating layer on the surface. The negative electrode material of the negative electrode sheet is a carbon material. The ID / IG of the carbon material is 0.3-0.
9. The electrolyte is an ether electrolyte.
2. A low CB value sodium ion battery according to claim 1, characterized in that: The moisture content of the positive electrode sheet is less than 150 ppm, the moisture content of the negative electrode sheet is less than 150 ppm, and the porosity of the negative electrode sheet is greater than 40%.
3. A low CB value sodium ion battery according to claim 1, characterized in that: The coating layer includes one or more of C, Al2O3, phosphate or sulfate.
4. A sodium ion battery with a low CB value according to any one of claims 1 to 3, characterized in that: The ether is diethylene glycol dimethyl ether or DME.
5. A low CB value sodium ion battery according to claim 4, characterized in that: The electrolyte also includes NaPF6 and NaBF4.
6. A low CB value sodium ion battery according to claim 5, characterized in that: The electrolyte also includes oxalate.
7. A low CB value sodium ion battery according to claim 6, characterized in that: The molar concentration ratio of NaPF6, NaBF4 and oxalate is 0.85-0.9:0.05-0.1:0.05-0.
1.
8. A low CB value sodium ion battery according to claim 6, characterized in that: The oxalate is one or more of sodium dioxalate difluorophosphate, LiBODFP, sodium bis(oxalate)borate, and sodium tri(oxalate)phosphate.
9. A sodium ion battery with a low CB value according to claim 1, characterized in that: 2g / Ah<The electrolyte injection coefficient is <3.8g / Ah.
10. A sodium ion battery with a low CB value according to claim 1, characterized in that: The puncture resistance of the diaphragm is greater than 500 gf.